2016
DOI: 10.1007/s00421-016-3475-y
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal and transcallosal modulation of unilateral and bilateral contractions of lower limbs

Abstract: Higher values of MEPs and VAL during bilateral contractions, in conjunction with unaltered SPs, do not support the concept of inhibition related to BLD, but rather suggest the possibility of cortical facilitation. Based on the existing literature, this behavior may be specific to the lower limb musculature, but the possibility of sub-cortical or higher-order neural alterations cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…The strength of the correlation may have been impacted by the slightly different testing positions and procedures between the two testing methods. The bilateral nature of the GroinBar may evoke a bilateral deficit phenomenon: the inability to generate maximal force when both limbs are operating simultaneously (22)(23)(24)(25), which could have impacted on the strength values. During HHD testing, athletes were also able to hold the side of the plinths however this was not reproduced with GroinBar testing, which is performed on the floor.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The strength of the correlation may have been impacted by the slightly different testing positions and procedures between the two testing methods. The bilateral nature of the GroinBar may evoke a bilateral deficit phenomenon: the inability to generate maximal force when both limbs are operating simultaneously (22)(23)(24)(25), which could have impacted on the strength values. During HHD testing, athletes were also able to hold the side of the plinths however this was not reproduced with GroinBar testing, which is performed on the floor.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The MT was defined as the minimal intensity needed to evoke an MEP of >200 μV in three out of five trials in the tonically active SOL (Škarabot et al., 2016), and MT showed a very high level of day‐to‐day reliability (day‐to‐day coefficient of variation of 4.40%) in our study.…”
Section: Methodsmentioning
confidence: 49%
“…Reportedly, knee extension BLD was present in the first test session, but there was no BI in a second session, suggesting a further lack of repeatability in the measure (Secher et al, 1988). Since the Secher et al’s (1988) study, no other work has reported lower extremity values in more than one test session, but studies have proposed that training may influence the BLD estimate (Howard & Enoka, 1991; Škarabot, Alfonso, et al, 2016). Using absolute peak values, this work reported the presence of knee extension facilitation (greater bilateral force than unilateral) in a bilaterally trained weightlifting group (BI = 6.6 ± 4.7), no BI in unilaterally trained group (BI = −6.6 ± 7.1) and BLD in an untrained group (−9.5 ± 6.8) (Howard & Enoka, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…When calculated by the average peak value, facilitation was no longer evident in the bilaterally trained group (Howard & Enoka, 1991). To further our argument, the aforementioned populations were later mimicked, reporting no BI across all groups (bilateral BI: −11.6 ± 16.0%; unilateral: −11.5 ± 10.5%; untrained: −4.5 ± 13.1%) using measures of averaged peak forces (Škarabot, Alfonso, et al, 2016). Such nuanced changes in calculation suggest there may be methodological flaws throughout prior BLD literature, influencing our present understanding of the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation